Strategic effects of service innovation on financial and market performance - Koçak Bilgin, Yasemin; Adıgüzel, Zafer (Management & Business Academy, 2021)
The reason for the emphasis on innovation and strategy was the need for organizations to be successful in performance criteria and growth aspirations against competitors. The fact that the competition continues to increase day by day and the entrance to the market is becoming more difficult in every sector shows the fact that companies need to improve their innovation skills in order to ensure sustainability in national or international activities. In the research, the effects of service innovation activities on financial and market performance, as well as strategic analysis and strategic orientation, are examined in banks which have a significant position in the service sector. The surveys were collected from 358 (white-collar) employees at the expert level, after the research model and the sector to be researched were determined. SPSS 25 and AMOS programs were used in the analysis, and the Sobel Test and Hayes process were used for mediation variable analysis. According to survey data, service innovation has a positive impact on both strategic orientation and strategic analysis, as well as financial and market performance. In addition, it is understood that strategic analysis and the mediation effect of strategic orientation variables exist.
Keywords: Service Innovation; Strategic Orientation; Strategic Analysis; Finance Performance; Market Performance; Innovation; Company Performance